2005
DOI: 10.1590/s1516-84842005000300005
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of chronic myeloid leukemia with imatinib mesylate in Brazil: a study of 98 cases

Abstract: Correspondence to : Vaneuza A. M. Funke Rua da Paz, 412, apt 151 -Centro 80060-160 -Curitiba-PR -Brazil Tel.: 055 41 3601000 -Fax: 055 41 3601015 E-mail: vaneuza@brturbo.com group. Rev. bras. hematol. hemoter. 2005;27(3):159-165.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
(21 reference statements)
0
8
0
6
Order By: Relevance
“…Unlike reports from high-resource countries, 33,39 the median age of our patients was only 35 years, which was similar to the median age of patients in the Brazilian study. 40 Shorter life expectancy in developing countries 41 or under diagnosis in the geriatric population may account for the younger age of our patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Unlike reports from high-resource countries, 33,39 the median age of our patients was only 35 years, which was similar to the median age of patients in the Brazilian study. 40 Shorter life expectancy in developing countries 41 or under diagnosis in the geriatric population may account for the younger age of our patients.…”
Section: Discussionmentioning
confidence: 96%
“…We could identify only 1 study from Brazil that reported results on imatinib in patients with CML. 40 Our patient population is not a selective population, because >95% of patients with CML across our country participate in 4 expanded-access programs. Most of our patients on IFN were unable to tolerate the recommended doses because of severe side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several publications have shown the results of treatment in similar groups (Kantarjian et al, 2004a,b;Funke et al, 2005;Lahaye et al, 2005). In this study, we analyzed patients at our institution who were treated with second-line IM and called them "pre-treated", as some were in late chronic phase (over a year since diagnosis) and others not.…”
Section: Discussionmentioning
confidence: 99%
“…Response was defined as major if the patient had a complete or partial response. Molecular response was described as previously defined (Kantarjian et al, 2002a;Hughes et al, 2003;Funke et al, 2005). Occurrence of events in patient outcome was defined as: death (any cause), progression to advanced stages of disease (accelerated phase and/or blast crisis) (Cortes and Kantarjian, 2003;Giles et al, 2004) and loss of responses (hematologic, cytogenetic or molecular).…”
Section: Study Design and Statistical Analysismentioning
confidence: 99%
“…Os eventos adversos nos pacientes que utilizaram esta droga são mínimos e se assemelham aos relatados na literatura, exceto pela menor incidência de sintomas gastrointestinais e cãimbras. 19 O imatinibe tem sido confirmado como terapia de primeira linha para a LMC por apresentar respostas duradouras na maior parte dos pacientes, principalmente nos que se encontram em fase crônica da doença; entretanto, alguns pacientes ainda em fase crônica e uma maior proporção em fases mais avançadas da LMC apresentam resistência ou intolerância ao imatinibe. 16,17,20,21 A resistência ao imatinibe pode ser desenvolvida por vários mecanismos moleculares, como a superexpressão de BCR-ABL, mutações no sítio de ligação BCR-ABL, entre outras; entretanto, os pontos de mutação no BCR-ABL constituem a ocorrência mais comum para a resistência a esta droga.…”
unclassified